DAMPAK UKURAN KORPORASI TERHADAP AUDIT FEE: KOMPARASI DI INDONESIA DAN MALAYSIA - Pramesti, Wahyu; Mahartantia, Nur Hidayah Ganda; Wijayati, Fitri Laela (BISNIS, 2018)
The aims of this study is to analyse the equalty of coeficient regression of corporation size on audit fee in Indonesia and Malaysia. Sample used in this study is companies who listed in BEI and Bursa Malaysia during 2013 – 2016. Using Chow Test to testing the equality of coeficient regression of corporate size on audit fee between Indonesia and Malaysia.Comparing the equality of coeficient regression of corporate size on audit fee in Indonesia and Malaysia. The result of this study show that corporation size has impact on audit fee in Indonesia and Malaysia.